A Systematic Review on the Evolution of Natural Mutation-dependent Antiviral Drug Resistance in Hepatitis C Virus (HCV) Genotypes Prevalent in Saudi Arabia: A Genomic and Therapeutic Perspective - Izhari, Mohammad Asrar (Natural Products Journal, The, 2025)
BackgroundThe characterization of resistance-associated amino acid substitution (RAAS) in direct-acting antivirals (DAA) molecular targets could reshape the treatment strategy for HCV infection. Hence, this review aimed to provide evidence on the impact of the RAASs on DAA treatment for HCV.MethodsPRISMA model was followed for the literature survey and evaluation (sources: PubMed, Sci-Hub, and Google Scholar). RAASs in DAA target proteins and their locations were mapped on 3-D proteins using two reference protein sequences: NS3/ID: AAA72945.1 and NS5A/NS5B/ID: NP_671491.1. NCBI-Basic Local Alignment Tool, UniProt and AlphaFold2/MMSeqs2, PyMol, and R-base/R-studio were used for alignment, retrieval of protein sequences, 3-D protein structure modeling, visualization of locations of RAASs, and diagrammatic representations, respectively.ResultsGenotype 4 afterwards genotype 1 was the most prevalent in Saudi Arabia. L2003M, Y2065N, M2000T, L2003V, and Q2002H RAASs were anti-NS5A inhibitor. NS5A-Q2002H was anti-daclatasvir in genotype 4. NS5A-Y2065H and NS5B-S2702T in genotype 1 were anti-sofosbuvir-resistant. NS3-A1182V, NS3-Q1106K/R, and NS3-T1080S RAASs exhibited resistance to double antivirals. NS3-D1194A RAAS was a multi-drug resistant variant (against 3 DAAs). NS3- V1062A, NS3-D1194G, NS3-D1194E/T, NS3- S1148R, NS3-V1196A, NS3-V1062LNS3-S1148A, and NS3-S1148G RAASs in genotype 1 were single drug-resistant variants. NS3- S1148R and NS3-S1148A in genotypes 2 and 5 were anti-simeprevir-resistant variants.ConclusionsAn array of identified RAASs, RAAS-dependent DAA treatment failure, and recommended combination DAA therapy in such clinical scenarios of RAASs are the significant outcomes of this research. RAAS-linked in vitro and in vivo resistance profiling at genotype/sub-genotype level will be crucial in treatment choice and for future DAA design strategies.
Keywords: NS5B